2020
DOI: 10.3892/ijmm.2020.4666
|View full text |Cite
|
Sign up to set email alerts
|

miR‑589‑3p sponged by the lncRNA TINCR inhibits the proliferation, migration and invasion and promotes the apoptosis of breast cancer cells by suppressing the Akt pathway via IGF1R

Abstract: The long non-coding (lnc)RNA named tissue differentiation inducing non-protein coding RNA (TINcR) is a tumor marker that has not been studied in breast cancer. The present study aimed to investigate the TINcR-targeting micro (mi)RNAs and the regulatory mechanisms of TINcR in breast cancer. Following prediction by TargetScan and confirmation by dual-luciferase reporter assay, TINcR was demonstrated to be a target gene for miR-589-3p. The expression of TINcR and miR-589-3p in breast cancer and adjacent tissues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…That work was then complemented by Guo et al’s recent research [ 72 ], which revealed TINCR effect in MCF-7 and MDA-MB-231 BC cell lines. TINCR over-expression there inhibited miR-589-3p activity because TINCR acted as the miR-589’s ceRNA.…”
Section: Long Non-coding Rnasmentioning
confidence: 90%
See 1 more Smart Citation
“…That work was then complemented by Guo et al’s recent research [ 72 ], which revealed TINCR effect in MCF-7 and MDA-MB-231 BC cell lines. TINCR over-expression there inhibited miR-589-3p activity because TINCR acted as the miR-589’s ceRNA.…”
Section: Long Non-coding Rnasmentioning
confidence: 90%
“…IGFR is a well-known trans-membrane tyrosine kinase receptor important in cell mitosis, proliferation, differentiation, apoptosis and regulation of Akt pathway activity [ 73 , 74 ]. Finally, Guo et al [ 72 ] determined that higher TINCR expression was associated with poor survival rate in a cohort of 68 patients.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…Insulin-like growth factor receptor 1 (IGFR-1), a tyrosine kinase cell surface receptor, is involved in the development and progression of breast cancer (210). Guo et al showed that TINCR played an oncogenic role in breast cancer through regulation of the miR-589-3p/IGF1R axis (126). Moreover, the expression of TINCR was higher in trastuzumab-resistant tissues than in sensitive tissues owing to enhanced histone acetylation of the TINCR promoter.…”
Section: Colon Cancer Associated Transcriptmentioning
confidence: 99%
“…Moreover, TINCR promoted EMT via downregulation of Snail-1 expression, while enhanced Snail-1 expression reversed EMT suppression induced by TINCR silencing in trastuzumab-resistant cell lines (127). Furthermore, Kaplan-Meier survival curves showed that high levels of tissue TINCR correlated with unfavorable prognosis in breast cancer (126). Wang et al found that circulating TINCR was dramatically elevated in breast cancer, particularly in the aggressive triple-negative subtype.…”
Section: Colon Cancer Associated Transcriptmentioning
confidence: 99%
See 1 more Smart Citation